Balanced harvesting: The institutional incompatibilities. (July 2016) - Pauly, Daniel; Froese, Rainer; Holt, Sidney J.
Abstract: Balanced harvesting is the name of a newly proposed approach to fishing which promises the extraction of high and sustainable fisheries yields while maintaining the structure of the ecosystem from which those yields could be obtained. This is to be achieved through exposing all components of ecosystems (from zooplankton to top predators, including seals, sea birds and marine mammals) to a fishing mortality proportional to their size-specific productivity. This study briefly analyses the incompatibility between balanced harvesting (and its implications) and the stated missions of two major organizations, FAO (which stresses the need of selective fishing in its Code of Conduct for Sustainable Fisheries ) and IUCN (which maintains the Red List of Threatened Species ), but which have issued reports or organized conferences promoting balanced harvesting. The study also demonstrates the incompatibility of balanced harvesting with the recently reformed Common Fisheries Policy of the European Union. While balanced harvesting appears partly compatible with declared fisheries policies of a few countries, e.g. with regard to whaling, sealing, and indiscriminate biomass fishing, it is not only incompatible with the basic tenets of fisheries science, but also with the vision, gradually emerging globally, that marine organisms such as marine mammals, sea turtles, sea-birds and other fauna have an intrinsic value and right to life that should not be undermined by more of the indiscriminate fishing which currently shapes much of our interactions with the oceans.